Wildlife Ecology and Conservation: Extension Programs and Faculty - William M. Giuliano; Emma V. Willcox (EDIS)
WEC299, a 4-page fact sheet by William Giuliano and Emma Willcox, Describes the department’s extension programs and provides a directory of extension faculty. Published by the UF Department of Wildlife Ecology and Conservation, November 2010.